Psycho-social construct characterization of adolescents food insecurity experience / Nazrul Hadi Ismail … [et al.] - Ismail, Nazrul Hadi; Md Nor, Norazmir; Masuri, Mohamad Ghazali; Md Isa, Khairil Anuar; Hashim, Nurhazirah (Research Management Institute, 2016)
Food insecurity that occurs when there is uncertain availability of future food, insufficiency in quantity and quality of food required for healthy life style or the need to use socially unacceptable ways to acquired foods, still remain a leading cause of morbidity and mortality worldwide. Previous study in rural Malaysian population has shown that more than 50% of the household were experiencing some sort of food insecurity. Obesity that was thought one of the consequences of food insecurity is the one that was blamed for the adverse health outcome such as diabetes, hypertension and cardiovascular event in those groups. However, current study has shown that the c-reactive protein is increased in the food insecured group showing evident of inflammatory action that lead to food insecurity-obesity paradox questionable. This study is sought to answer weather the nutritional status and its impact on inflammatory pathway, oxidative stress,PPARs' and also immunological processes may help explain how individual experiencing food insecurity influences health outcomes such as cardiovascular diseases. For that purposes, the effect of food insecurity on inflammatory markers such as tumour necrosis factor-a, c-reactive protein and interleukin-6 will be studied. Oxidative stress biomarkers such as F2- isoprostane and malonaldehyde will be measured. PPARs also wiil be enumerated. Furthermore specific nutritional markers that associated with inflammatory state and innate immune function will also be analyses such as vitamin A, vitamin B12, and folate. Finally full blood count with CD4+ and CD8+ measurement will also evaluated. The structured equation model (SEM) will further be used to help explain those relationship if any. The results of this research could help scientist to understand the alternative pathway that might explain the potential route through which food insecurity is associated with adverse health outcome, and therefore can further suggest for the development of more effective public health program.